Comprehensive view on occupational health and safety as a part of responsible rewarding - Klimkiewicz, Katarzyna; Ewa Beck-Krala (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The concept of Corporate Social Responsibility (CSR) has a tremendous impact on the Human Capital Management, which is manifested in new trends in rewarding, such as responsible rewarding or total rewards approach. These approaches based on the assumptions of Corporate Social Responsibility promote the need for a holistic view on a human and therefore emphasize the working environment as an important aspect of the comprehensive employee rewarding policy within an organization. The aim of this paper is thus to raise awareness of the role that a supportive working environment and occupational health and safety (OSH) in particular play today in the effective and responsible employee management. The authors show an integrated view of OSH as a part of employee responsible rewarding. In this context, responsible rewarding takes into account the important issue of healthy and safe working conditions. This broad perception of employee rewarding allows the creation of a supportive work environment and strengthens the safety culture within the organization
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 464, s. 69-79
Keywords: responsible rewarding; occupational health and safety; human capital; corporate social responsibility; odpowiedzialne wynagradzanie; bezpieczeństwo i higiena pracy; kapitał ludzki; społeczna odpowiedzialność przedsiębiorstw